2021
DOI: 10.1186/s40359-021-00519-4
|View full text |Cite
|
Sign up to set email alerts
|

An integrative counselling program to promote active ageing for older people in Thai nursing homes: an intervention mixed methods design

Abstract: Background Active ageing has been a rapidly developing field of study in light of the growing population of older people. Acknowledgement of the lack of a counselling program to promote active ageing for the older people in nursing homes led to the development of this study which aims to investigate active ageing of the Thai elderly in a nursing home in addition to promoting active ageing for them through integrative counselling. Methods The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It was also found that Thai elderly with chronic diseases and depression that had high resilience would have high patience, problemsolving ability, and mental and social dependence, especially rural Thai elderly who depend on their grandchildren to take care of them. These would promote the well-being and quality of life of the elderly in Thailand [38], which is different from the elderly abroad who have the potential to be selfcare and self-reliant [39]. Therefore, the researchers developed a resilience scale suitable for the context of Thai elderly with chronic diseases and depression.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that Thai elderly with chronic diseases and depression that had high resilience would have high patience, problemsolving ability, and mental and social dependence, especially rural Thai elderly who depend on their grandchildren to take care of them. These would promote the well-being and quality of life of the elderly in Thailand [38], which is different from the elderly abroad who have the potential to be selfcare and self-reliant [39]. Therefore, the researchers developed a resilience scale suitable for the context of Thai elderly with chronic diseases and depression.…”
Section: Discussionmentioning
confidence: 99%
“…3) Two experts conducted peer debriefing. The researcher exchanged and discussed the information with experts to refine data categorizing [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thailand is at the brink of becoming a full‐fledge aging society, with the number of elder citizens rapidly increasing. Elderly population (defined as age 60 or over) in 2021 indeed accounted for more than 20% of the total Thai population (Juthavantana, Sakunpong, Prasertsin, Charupheng, & Lau, 2021). As people age, the body functionalities naturally deteriorate.…”
Section: Introductionmentioning
confidence: 99%